A Study of Entrepreneurship Development in Bangladesh: Pros and Cons - Chowdhury, Fatema Nusrat (Journal of Asian Scientific Research, 2017)
This study aims to explore the opportunities which encourages people to become entrepreneurs, in microcosm such extensive constrains related to growth and development of entrepreneurship in Bangladesh. The paper is covered by secondary data collected from research article, monographs, cases and various published materials on the subject. The findings indicated that new scope and existing opportunities for entrepreneur from the government, socio-cultural perspective, natural deposit. The outspread list of constrains and problems of entrepreneurship development include personal, environmental- situational, judicial, economic and political. The study also refers some suggestions for utilizing the opportunities overcoming those constrains for entrepreneurship development in Bangladesh.